Corundum-type Fe-doped cathodic arc evaporated Al–Cr–O coatings. (1st March 2015) - Koller, C.M.; Ramm, J.; Kolozsvári, S.; Munnik, F.; Paulitsch, J.; Mayrhofer, P.H.
Abstract : A quaternary alloying approach comprising the addition of 1–5 at.% Fe to Al0.7 Cr0.3 targets for cathodic arc evaporation at 550 °C is investigated regarding its influence on promoting single-phase α-(Al, Cr)2 O3 film growth. Based on detailed X-ray diffraction and transmission electron microscopy studies we can show that the α-phase fraction correlates with the incorporated Fe content and continuously extends with increasing film thickness at the expense of the cubic phases.